CGRP-dependent and independent mechanisms of acute and persistent post-traumatic headache following mild traumatic brain injury in mice. (December 2019) - Navratilova, Edita; Rau, Jill; Oyarzo, Janice; Tien, Jason; Mackenzie, Kimberly; Stratton, Jennifer; Remeniuk, Bethany; Schwedt, Todd; Anderson, Trent; Dodick, David; Porreca, Frank
Background: Acute and persistent post-traumatic headache are often debilitating consequences of traumatic brain injury. Underlying physiological mechanisms of post-traumatic headache and its persistence remain unknown, and there are currently no approved therapies for these conditions. Post-traumatic headache often presents with a migraine-like phenotype. As calcitonin-gene related peptide promotes migraine headache, we explored the efficacy and timing of intervention with an anti- calcitonin-gene related peptide monoclonal antibody in novel preclinical models of acute post-traumatic headache and persistent post-traumatic headache following a mild traumatic brain injury event in mice. Methods: Male, C57Bl/6 J mice received a sham procedure or mild traumatic brain injury resulting from a weight drop that allowed free head rotation while under minimal anesthesia. Periorbital and hindpaw tactile stimulation were used to assess mild traumatic brain injury-induced cutaneous allodynia. Two weeks after the injury, mice were challenged with stress, a common aggravator of migraine and post-traumatic headache, by exposure to bright lights (i.e. bright light stress) and cutaneous allodynia was measured hourly for 5 hours. A murine anti- calcitonin-gene related peptide monoclonal antibody was administered after mild traumatic brain injury at different time points to allow evaluation of the consequences of either early and sustained calcitonin-gene related peptide sequestration or late administration only prior to bright light stress. Results: Mice with mild traumatic brain injury, but not a sham procedure, exhibited both periorbital and hindpaw cutaneous allodynia that resolved by post-injury day 13. Following resolution of injury-induced cutaneous allodynia, exposure to bright light stress re-instated periorbital and hindpaw cutaneous allodynia in injured, but not sham mice. Repeated administration of anti-calcitonin-gene related peptide monoclonal antibody at 2 hours, 7 and 14 days post mild traumatic brain injury significantly attenuated the expression of cutaneous allodynia when evaluated over the 14-day post injury time course and also prevented bright light stress-induced cutaneous allodynia in injured mice. Administration of anti-calcitonin-gene related peptide monoclonal antibody only at 2 hours and 7 days after mild traumatic brain injury blocked injury-induced cutaneous allodynia and partially prevented bright light stress-induced cutaneous allodynia. A single administration of anti-calcitonin-gene related peptide monoclonal antibody after the resolution of the peak injury-induced cutaneous allodynia, but prior to bright light stress challenge, did not prevent bright light stress-induced cutaneous allodynia. Conclusions: We used a clinically relevant mild traumatic brain injury event in mice along with a provocative stimulus as novel models of acute post-traumatic headache and persistent post-traumatic headache. Following mild traumatic brain injury, mice demonstrated transient periorbital and hindpaw cutaneous allodynia suggestive of post-traumatic headache-related pain and establishment of central sensitization. Following resolution of injury-induced cutaneous allodynia, exposure to bright light stress re-established cutaneous allodynia, suggestive of persistent post-traumatic headache-related pain. Continuous early sequestration of calcitonin-gene related peptide prevented both acute post-traumatic headache and persistent post-traumatic headache. In contrast, delayed anti-calcitonin-gene related peptide monoclonal antibody treatment following establishment of central sensitization was ineffective in preventing persistent post-traumatic headache. These observations suggest that mechanisms involving calcitonin-gene related peptide underlie the expression of acute post-traumatic headache, and drive the development of central sensitization, increasing vulnerability to headache triggers and promoting persistent post-traumatic headache. Early and continuous calcitonin-gene related peptide blockade following mild traumatic brain injury may represent a viable treatment option for post-traumatic headache and for the prevention of post-traumatic headache persistence. Abbreviations: CA Cutaneous allodynia CGRP Calcitonin gene-related peptide mTBI Mild traumatic brain injury PTH Post-traumatic headache APTH Acute post-traumatic headache PPTH Persistent post-traumatic headache